e-Integral map as an interactive procedural learning tool / Nor Hazizah Julaihi... [et al] - Julaihi, Nor Hazizah; Li Li, Voon; Eng, Tang Howe (Faculty of Computer and Mathematical Sciences, 2014)
In higher learning institutions, students have been learning Calculus conventionally from textbook or reference book which they perceived as abstract, confusing and cannot be imagined. Available books are too complicated for fast revision, too complex for identification of appropriate technique(s) to solve Calculus problems and fail to provide a thorough overview on the content learned. This study proposes e-integral Map which provides an alternative way for the learners to learn Calculus interactively. This study attempts to investigate the effectiveness of using e-integral Map in Calculus learning among higher learning institutions students. Students' understanding and students' feedback while and after using e-integral Map are also investigated in this study, e-integral Map provides a rich learning experience to cater the different abilities of students in learning Calculus. This study employs mixed methods research design in which quantitative procedures that involve the uses of questionnaires, pre-test and post-test, is the initial method of collecting data and follow-up by the collection of interview data to provide in-depth information of the quantitative findings. A total of 55 higher learning institution students will be selected by using the stratified random sampling method. The sample will be randomly assigned to treatment and control groups. Six respondents will then be interviewed to tackle the learning process and the experience of the students while using e-integral map. The findings will then be analysed. The expected outcomes from this study comprise an innovative and new teaching and learning method to assist students' in learning Calculus.